2008
DOI: 10.1007/s11606-008-0791-x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Team-Based Care: Impact of Physician-Pharmacist Collaboration on Uncontrolled Hypertension

Abstract: OBJECTIVE: Evaluate the effectiveness of collaborative management of hypertension by primary carepharmacist teams in community-based clinics.STUDY DESIGN: A 12-month prospective, single-blind, randomized, controlled trial in the Providence Primary Care Research Network of patients with hypertension and uncontrolled blood pressure. METHODS:As compared to usual primary care, intervention consisted of pharmacy practitioners participating in the active management of hypertension in the primary care office accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
151
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 22 publications
2
151
0
1
Order By: Relevance
“…12 Some studies have shown that pharmacist participation in designing, implementing, and monitoring therapeutic programs in patients with CVD or CV risk factors could (a) improve the patient's knowledge, 13 (b) facilitate adoption of and outcomes from lifestyle interventions, 14 (c) improve the identification of candidates and the results of primary 15 or secondary 16 prevention, and (d) increase the percentage of patients with high CV risk who achieve the goals related to BP [17][18][19][20] and lipid 9,21 levels. In contrast, other randomized controlled trials (RCTs) have found that community pharmacist intervention did not lead to improvements in primary outcome measures (e.g., hospital admissions 22 or the proportion of patients receiving appropriate medication 23 ).…”
Section: Effectiveness Of Dader Methods For Pharmaceutical Care On Conmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Some studies have shown that pharmacist participation in designing, implementing, and monitoring therapeutic programs in patients with CVD or CV risk factors could (a) improve the patient's knowledge, 13 (b) facilitate adoption of and outcomes from lifestyle interventions, 14 (c) improve the identification of candidates and the results of primary 15 or secondary 16 prevention, and (d) increase the percentage of patients with high CV risk who achieve the goals related to BP [17][18][19][20] and lipid 9,21 levels. In contrast, other randomized controlled trials (RCTs) have found that community pharmacist intervention did not lead to improvements in primary outcome measures (e.g., hospital admissions 22 or the proportion of patients receiving appropriate medication 23 ).…”
Section: Effectiveness Of Dader Methods For Pharmaceutical Care On Conmentioning
confidence: 99%
“…In a 12-month, prospective, single-blind RCT by Hunt et al (2008), designed to evaluate the effectiveness of collaborative management of hypertension by primary care-pharmacist teams in community-based clinics, patients with uncontrolled hypertension were randomized to a physician-pharmacist collaborative model of care intervention (n = 230) or to usual primary care (n = 233). 18 According to an intention-to-treat analysis in which chart review was used to obtain the last recorded blood pressure values if the patient missed the last clinic visit, this study reported that 54% (125/230) of the patients in the intervention group achieved BP goals, compared with 42% (97/233) of the patients in the control group (P = 0.005).…”
Section: Effectiveness Of Dader Methods For Pharmaceutical Care On Conmentioning
confidence: 99%
See 1 more Smart Citation
“…Partnerships and coalitions with public-and privatesector organizations: Partnerships and coalition-building with the private sector as well all levels of the public sector (local, state, and federal) will drive the importance of pharmacist-delivered MTM, enhance pharmacists role in collaborative teambased care, as well as demonstrate the public health importance of pharmacists in many health and wellness activities. 29 Specific partnerships to establish include the American Public Health Association and HealthyPeople 2020.…”
Section: Wellness and Preventionmentioning
confidence: 99%
“…The need for and effectiveness of pharmacists in interprofessional and collaborative team-based care roles have been envisioned and supported in the literature. 26,27,28,29,34 Pharmacists belonging to PCMH teams will also be called upon to track and manage care, provide self-care education to patients, and track patient progress in managing their health. These activities are not only critical to promoting health and wellness but also for pharmacists to enhance the visibility, value, and importance of pharmacy and pharmacist in individual and population-level outcomes through education, research and service.…”
Section: Wellness and Preventionmentioning
confidence: 99%